Economic Impact of Leasing on Lessees in Jaffna District of Sri Lanka - Thavaseelan, Rajan; Krishnapillai, Sooriyakumar; Santhirasegaram, Selvarathnam (International Journal of Economics and Financial Issues, 2021)
This study examines the impact of leasing on lessee’s income, family expenditure and default rate in Jaffna District which was badly affected by the civil war from 1983 to 2009. This war has significantly affected the socioeconomic status of the people living in the area. Since the end of the war, the presence of the financial institutions has been increased significantly in the district. There are 39 financial institutions operating in Jaffna district and all of them have the function of leasing as their major operation. In general, service sector contributes 65% of the economy in Jaffna district. Transport service is also playing an important role in the economy of the district. Domestic tourism slowly emerges as a significant economic activity in this district. For this study, 331 leasing clients were randomly selected to collect data using pre tested questionnaire. The study has found that 72.8% of leasing facilities has been offered to transport sector and out of the leased facilities 39.9% were seized. Multiple regression models for lessee’s income and family expenditure and probit model for default rate of leasing were developed to study effect of leasing on lessee’s income, family expenditure and default rate. The results show that leasing has positive impact on income and family expenditure. On average, family expenditure increased by leasing is greater than the income increased by leasing because most of the lessees are economically marginalized. Therefore, there is higher possibility to get default but increase in leasing amount decrease the default rate. Leasing had greater positive income effect on self-employed clients using leasing in their own business. It was found that the leasing companies are charging very high interest rate and penalty on delayed installments. Leasing companies need to assess the client’s potentials and repayment capacity before offering leasing facility. Leasing companies should provide more grace period when the clients are in trouble. It is recommended to offer more leasing facilities to other sectors such as fisheries, agriculture and industries. Keywords: Leasing facility, Multiple linear regression, Socio-economic impact JEL Classifications: G21, D25, D14, O12 DOI: https://doi.org/10.32479/ijefi.10885